New data on the biography and pastoral itinerary of Juan Pérez Bocanegra - Viola Casalongüe, Gabriel (2010)
This study presents the most complete list of biographical data to date on the Peruvian priest Juan Pérez Bocanegra (ca. 1560-1570 - ca. 1634-1645). The references of his ecclesiastical career are offered: studies in the seminary of San Antonio Abad (Cusco), parish priest of Belén (Cusco), parish priest of San Pedro Apóstol de Andahuaylillas, cantor in the Cathedral of Cusco and official examiner of the diocese in Quechua and Aymara. After reviewing the previous investigations and the biographical elements of his Ritual form and instruction of cures, from 1631, the author provides new data from unpublished documents from Cusco and Andahuaylillas.